Pengembangan Media Pembelajaran Interaktif Berbasis Android Menggunakan Smart Apps Creator pada Mata Pelajaran IPA Kelas VIII SMP Negeri 4 Dua Pitue - Suryandi, Wahyu; Suciana Adam, Nurul; Baharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was designed to produce Android-based interactive learning media for Grade VIII science, particularly on water, air, and soil pollution, and to assess its validity, practicality, and effectiveness. A Research and Development approach was applied through the 4D model, adapted into three phases: define, design, and develop. The product trial involved two expert validators, consisting of one media expert and one subject-matter expert, two science teachers, and 27 students from class VIII.3 at SMP Negeri 4 Dua Pitue. Data were gathered using observation, interviews, validation sheets, user-response questionnaires, and learning outcome tests. The data were examined with qualitative and quantitative descriptive analysis. The final product was an Android application that presents competencies, concept maps, learning content, practice questions, images, animations, audio, and task-submission links. Expert appraisal obtained an overall mean score of 4.4, which falls into the very valid category. Teacher responses produced a mean score of 4.2 and were classified as practical, while student responses reached 4.6 and were categorized as very practical. The achievement test indicated that 23 out of 27 students met the mastery criterion, with an 85% mastery rate. These results show that the Android-based interactive learning media is appropriate, practical, and effective as a supplementary medium for teaching science on environmental pollution.